Influencia de los programas televisivos violentos en el comportamiento de los niños de 5 a 8 años de edad, de la unidad educativa “Manuela Cañizares”, del cantón pasaje, periodo lectivo 2013 – 2014 - Díaz Pérez, Lorena Estefanía (2015)
This research paper presents a study on the level of influence of television children's programs on children / as of 5 to 8 years of age Education Unit "Manuela Cañizares" to propose alternative strategies for solving the teachers and parents family in behavioral development of children taking advantage and making good use of children's television programs. Parents are especially concerned about the hours their children spend in front of the screen, by the programs they watch, the content, the values, the possible effects of a violent scene. However, they forget that television can become isolated from the context of reception and in a violent world, wars, famines, misery, attacks, disasters, terrorism and conflict, television can not be solely responsible for what they feel and live the kids. The answers offered are in all cases, a common starting point: sharing the television consumption of the boys know they see, know the favorite programs, see them with them from time to time and, above all, ask, listen and dialogue .